Investigation Of Wave Propagation To PV-Solar Panel Due To Lightning Induced Overvoltage - Abdul Rahim , Nur Hidayu; Baharudin, Zikri Abadi; Othman, Md Nazri; Zakaria, Zahriladha; Ahmad Khiar, Mohd Shahril; Saharuddin, Nur Zawani; Ahmad, Azlinda (Universitas Ahmad Dahlan (UAD) and Institute of Advanced Engineering and Science (IAES), 2014)
-